Streptozotocin‐Induced Diabetic Models in Mice and Rats - Furman, Brian L. (Current protocols, 2021)
Streptozotocin (STZ) is an antibiotic that causes pancreatic islet β‐cell destruction and is widely used experimentally to produce a model of type 1 diabetes mellitus (T1DM). Detailed in this article are protocols for producing STZ‐induced insulin deficiency and hyperglycemia in mice and rats. Also described are protocols for creating animal models for type 2 diabetes using STZ. These animals are employed for assessing the pathological consequences of diabetes and for screening potential therapies for the treatment of this condition. © 2021 The Authors.